The role of fossils in the microfacies studies and recognizing the sequence boundaries of the Qom Formation: A case study in Ghasr-e-Bahram Section, northwest part of Siahkuh, south Garmsar - Jahanbakhash Daneshian; Maryam Derakhshani (Journal of Stratigraphy and Sedimentology Researches)
Abstract Sequence stratigraphy is a branch of stratigraphy that can enable us to correlate deposits with considerable accuracy. This research aims to investigate the role of fossils in the recognition of system tracts and sequence boundaries along succession using microfacies features. To achieve this aim, we studied the Qom Formation at the Qasr-e-Bahram section located in the south of Garmsar. This formation is mainly composed of argillaceous limestones, limestones, and marls, overlies the Lower Red Formation, and lies under the Upper Red Formation disconformably. Based on paleontological studies, the suggested age is the Late Aquitanian to Burdigalian (Early Miocene). The microfacies analysis indicates a variety of facies and environments (lagoon, carbonate barrier, and open marine). The significant presence of red algal with other reef-forming elements within microfacies as well as the presence of turbidite facies probably implies a shelf carbonate platform. According to geological field and laboratory studies, deposits of the Qom Formation include four third-order depositional sequences, and the presence and abundance of fossils such as foraminifera, algae, bryozoans, and corals were useful tools in identifying the systems tracts and their boundaries. Keywords: Qom Formation, Early Miocene, Shelf, Sequence biostratigraphy, South Garmsar.